Does Sterilization Policy Exert an Upward Pressure on Interest Rate as Dictated by Theory? A Nigerian Example - Chile, Nzeh, Innocent; Collins, Nwogwugwu, Uche; Edith, Nkamnebe, Ogochukwu; Eze, Millicent Adanne; Yusuf, Abubakar; Okafor, Bartholomew.O.N. (Asian Journal of Economics and Empirical Research, 2021)
The implications of capital inflows on the economy and the fall out of the policy geared towards addressing these phenomena, especially the impact of the policy on interest rate motivated us in this study. Under the framework of ARDL and using monthly series over a period of 2010M1-2021M3, our findings showed that in the short-run, sterilization policy leads to rising interest rate in the current period. However, after a lag, sterilization policy depresses interest rate. We equally found that in the long-run, sterilization policy pushes interest rate up. In another direction, we observed a negative relationship between money supply and interest rate both in the short-run and in the long-run and the exogenous variables in the model influence interest rate significantly. We therefore recommend that different measures should be adopted to cushion the effect of unsustainable capital inflows to avoid repeated need for further sterilization and the increasing cost of sterilization in the long-run. It is also our advice that exogenous variables should be factored in when fashioning out a desirable interest rate in line with economic reality.